Rehabilitacja ducha - Kuźniarz, Bartosz (Er(r)go. Teoria - Literatura - Kultura, 2003)
Bartosz Kuźniarz “The Rehabilitation of the Spirit” Drawing from the elements of Niklas Luhmann’s theory, the article analyses cultural communication as the foundation of social life and self-reproduction of social systems.